Terminal ileum herniation through the broad ligament as rare cause of small bowel perforation - Izhar, NA; Shamil, S; Malek, M; Elagili, Faisal; Md Nor, Azmi (2023)
INTRODUCTION: Obstruction and perforation of small bowel due to internal herniation into the broad ligament is a rare. To the best of our knowledge, this is the third case report in the literature. OBJECTIVE: We report a case of small bowel herniated through broad ligament causing obstruction and perforation. REPORT A 38-year-old female with history of recent lower segment caesarean section, presented with nausea, abdominal pain and distention for 11 days prior. Clinically she was dehydrated, the abdomen was distended and tender but there was no peritonism. Abdomen X-ray show dilated small bowel. Contrast enhanced CT abdomen showed generalized dilation of small bowel most likely due to adhesion band. Emergency laparotomy was performed and noted small bowel was herniated and strangulated into a broad ligament defect with 2cm perforation at the terminal ileum. The attachment of the broad ligament then was released from the lateral peritoneal wall and limited right hemicolectomy with primary anastomosis was performed. Patient was discharged well post operatively. CONCLUSION Strangulated Small bowel broad ligament hernias are rare and challenging to diagnose preoperatively. Despite history of abdominal surgery, internal herniation should be considered before opting conservative treatment.